ASJO 2021
DOI: 10.1055/s-0040-1718979
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of HIV-1p24 in Detecting the Presence of HIV Infection in Histopathology Tissue Specimens

Abstract: Introduction HIV (human immunodeficiency virus)-associated immunodeficiency is the single most important acquired immunodeficiency in humans, underlying several diseases. The presence of HIV infection may be unsuspected or undetected in tissues due to latency or failure of the consulting physician to document it on the requisition form. HIV-1p24 protein is a component of the HIV particle capsid that can be exploited serologically and immunohistochemically to detect the presence of HIV infection. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…31 Germinal center follicular dendritic cells are the most reliable cells to express the p24 antigen in FFPE tissue derived from HIV-infected individuals. 58,59 Staining is also demonstrated in the mantle zone, intrafollicular and paracortical lymphocytes in lymphoid tissue. P24 staining has not been reported in epithelial cells, stromal cells and plasma cells.…”
Section: Discussionmentioning
confidence: 94%
“…31 Germinal center follicular dendritic cells are the most reliable cells to express the p24 antigen in FFPE tissue derived from HIV-infected individuals. 58,59 Staining is also demonstrated in the mantle zone, intrafollicular and paracortical lymphocytes in lymphoid tissue. P24 staining has not been reported in epithelial cells, stromal cells and plasma cells.…”
Section: Discussionmentioning
confidence: 94%
“…Although the morphologic picture is characteristic, immunohistochemistry remains indispensible for the exclusion of the several morphologic mimickers [9,10]. Studies have also shown that the presence of HIV infection can be detected in archived histopathology specimen using HIV-1p24 immunohistochemical stain [11,12]. This can therefore be exploited in classifying KS into two tiers: HIV/AIDS associated and non-HIV/AIDS associated.…”
Section: Introductionmentioning
confidence: 99%